Sight unseen [compact disc, unabridged] : a novel - Johansen, Iris (Johansen, Iris. Kendra Michaels series., 2014)
A deadly multi-vehicle pile-up on San Diego's historic Cabrillo bridge is thought of as a horrific accident; until Kendra Michaels arrives on the scene and perceives it as something much more sinister. Blind for decades and now sighted, Kendra's unusual skill for observation is highly sought after by both the FBI and CIA. Now her amazing conclusions open up a multi-jurisdictional investigation that once again teams her with the FBI and federal agent Adam Kyle.